Akuisisi Bukti Digital Aplikasi Viber Menggunakan Metode National Institute of Standards Technology (NIST) - Syahib, Muhammad Irwan; Riadi, Imam; Umar, Rusydi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The rapid development of mobile technology today is directly proportional to the development of mobile applications in it. Making it easier for people to choose and use the application as they want. This has resulted in misuse of negative things, ranging from human trafficking, drug trafficking, as well as online prostitution business. Viber is an Instant Messenger application that makes it easy for users. This application can be used to send messages, call, send photos, audio and video to others. This application has been used by 260 million people worldwide. This is the basis of research to acquire digital evidence in Viber applications. Data obtained after acquiring based on the work steps of NIST are the accounts of the perpetrators, contacts targeted by the perpetrators, call history, text messages, picture messages and videos.